2021
DOI: 10.1016/j.isci.2021.102077
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol inhibits intestinal lipid absorption by reprofiling the gut microbiota to attenuate high-fat diet-induced obesity

Abstract: Summary Celastrol, a compound extracted from traditional Chinese medicine, has been reported as a potent anti-obesity agent with controversial mechanisms. Here both C57BL/6J and leptin-deficient ( ob/ob ) mice fed a high-fat diet (HFD) displayed body weight loss after celastrol therapy, opposing the previous viewpoint that celastrol improves obesity by sensitizing leptin signaling. More importantly, celastrol downregulated lipid transporters in the intestine, increased lipid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 71 publications
2
28
0
Order By: Relevance
“…Antibiotic treatment, in general, alleviated HFD-induced abnormalities in lipid profiles, oxidative stress and inflammation status (Fig. 5A-W), in line with other studies, 33,34 and most intriguingly, it significantly attenuated the protective effect of WEFL on hepatocytes. No significant difference was…”
Section: Gut Microbiota Are Required For the Beneficial Effects Of Wefl And Butyric Acid May Help Explain The Protective Functionsupporting
confidence: 89%
“…Antibiotic treatment, in general, alleviated HFD-induced abnormalities in lipid profiles, oxidative stress and inflammation status (Fig. 5A-W), in line with other studies, 33,34 and most intriguingly, it significantly attenuated the protective effect of WEFL on hepatocytes. No significant difference was…”
Section: Gut Microbiota Are Required For the Beneficial Effects Of Wefl And Butyric Acid May Help Explain The Protective Functionsupporting
confidence: 89%
“…In particular, M-LB/CS significantly increased the fecal excretion of cholesterol and triglyceride. It has been reported that black tea polyphenols, oolong tea extract, celastrol, montmorillonite, and orlistat can attenuate diet-induced obesity via accelerating fecal excretion of lipids [ 3 , 55 , 56 , 57 , 58 ]. Inhibition of pancreatic lipase, downregulation of intestinal transporter for fatty acids and cholesterols, and alteration of intestinal microbiota have been suggested as possible mechanisms for enhancing fecal lipid excretion via inhibition of lipid absorption [ 3 , 55 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that black tea polyphenols, oolong tea extract, celastrol, montmorillonite, and orlistat can attenuate diet-induced obesity via accelerating fecal excretion of lipids [ 3 , 55 , 56 , 57 , 58 ]. Inhibition of pancreatic lipase, downregulation of intestinal transporter for fatty acids and cholesterols, and alteration of intestinal microbiota have been suggested as possible mechanisms for enhancing fecal lipid excretion via inhibition of lipid absorption [ 3 , 55 , 59 ]. Although detailed mechanisms for M-LB/CS must be further established, the increase in fecal lipids excretion by M-LB/CS will serve one of the plausible mechanisms to explain the anti-obesity activity of M-LB/CS through alleviating the abnormal accumulation of lipids in the blood that occurs in HFD-induced obesity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging tools such as 16S rRNA gene sequencing, untargeted and targeted metabolomics, and host RNA sequencing, we uncovered distinct diet- and gut microbe-dependent metabolites and their associated impact on the hepatic transcriptome. Important to note, limitations of this study include but are not limited to the fact that antibiotic ablation does not completely eliminate the gut bacterial community and has been reported to reduce dietary lipid absorption in rats and mice [ 82 , 83 ]. The use of germ-free mice would offer a more rigorous method to study the microbial aspect in terms of metabolites and ruling out hepatic transcriptional changes due to the antibiotics themselves.…”
Section: Discussionmentioning
confidence: 99%